Heidelberg Ion Therapy Center (HIT): Initial clinical experience in the first 80 patients - Combs, Stephanie; Ellerbrock, Malte; Haberer, Thomas; Habermehl, Daniel; Höss, Angelika; Jäkel, Oliver; Jensen, Alexandra; Klemm-Meyer, Swantje; Münter, Marc; Naumann, Jakob; Nikoghosyan, Anna; Oertel, Susanne; et al. (Acta oncologica, 2010)
The Heidelberg Ion Therapy Center (HIT) started clinical operation in November 2009. In this report we present the first 80 patients treated with proton and carbon ion radiotherapy and describe patient selection, treatment planning and daily treatment for different indications. - PATIENTS AND METHODS: Between November 15, 2009 and April 15, 2010, 80 patients were treated at the Heidelberg Ion Therapy Center (HIT) with carbon ion and proton radiotherapy. Main treated indications consisted of skull base chordoma (n = 9) and chondrosarcoma (n = 18), malignant salivary gland tumors (n=29), chordomas of the sacrum (n = 5), low grade glioma (n=3), primary and recurrent malignant astrocytoma and glioblastoma (n=7) and well as osteosarcoma (n = 3). Of these patients, four pediatric patients aged under 18 years were treated. - RESULTS: All patients were treated using the intensity-modulated rasterscanning technique. Seventy six patients were treated with carbon ions (95%), and four patients were treated with protons. In all patients x-ray imaging was performed prior to each fraction. Treatment concepts were based on the initial experiences with carbon ion therapy at the Gesellschaft für Schwerionenforschung (GSI) including carbon-only treatments and carbon-boost treatments with photon-IMRT. The average time per fraction in the treatment room per patient was 29 minutes; for irradiation only, the mean time including all patients was 16 minutes. Position verification was performed prior to every treatment fraction with orthogonal x-ray imaging. - CONCLUSION: Particle therapy could be included successfully into the clinical routine at the Department of Radiation Oncology in Heidelberg. Numerous clinical trials will subsequently be initiated to precisely define the role of proton and carbon ion radiotherapy in radiation oncology.